Teen Advisory Council Survey's Factors Associated With Self-Harming Thoughts - McPherson, Pamela; Alderman, Laura Lane; Temple, Jazzlynn; Lawrence, Robert; Avila-Quintero, Victor J.; Magner, Johnette; Sagrera, Caroline E.; Patterson, James C.; Murnane, Kevin S. (Frontiers in Psychiatry, 2022)
Background The evaluation of teens with self-harming thoughts (SHT) is a high-stakes task for physicians in community and emergency department (ED) settings. The lived experience of adolescents with stress and SHT provides an important source of insight for mental health professionals who evaluate and treat teens A snapshot of the lived experience of teens in northwest Louisiana was captured by the Step Forward Teen Advisory Council (TAC) in 2019. The TAC surveyed peers with the goal of identifying common stressors experienced by local teens in order to inform policy and practices in the local school system. The identification of stressors is a critical step in addressing SHT as adolescents who experience life stressors are at increased risk for self-harming thoughts (SHT), a known precursor to self-harm and suicide. Assessing youth for life stressors is a critical element of suicide prevention. Methods Local teens queried 5,070 peers attending Caddo Parish schools to better understand the stressors faced by high school students in Northwest Louisiana using a student developed survey. Results were presented to peers at a virtual summit where teens developed action items to reduce stress and presented findings to local leaders. Their efforts ultimately lead to increased supports for students in local schools. Results Over half of the teens surveyed reported stressors that negatively impacted their physical or emotional well-being. Students endorsing self-harming thoughts reported an average of 7.82 stressors as compared to 3.47 in peers without SHT. Teens with stressors at both home and school were more likely to experience SHT than teens with stressors in a single location. Conclusion The Gen Z students who developed the TAC Survey identified stress as a major concern for teens in Northwest Louisiana. The TAC Survey data aligns local experience with established data regarding the association between stress, depression and SHT. Second, the results highlight the importance of diving deep to identify all stressors when assessing the risk of self-harm. Finally, the lived experience of local teens with SHT provides critical information for professionals to better understand risk for SHT and suicide in our region and beyond.